Prehospital extracorporeal cardiopulmonary resuscitation for out‐of‐hospital cardiac arrest: A retrospective eligibility study. (1st July 2019) - Kilner, Thomas; Stanton, Benjamin L; Mazur, Stefan M
Abstract: Objective: We sought to identify out‐of‐hospital cardiac arrest (OOHCA) patients who might benefit from a future prehospital extracorporeal cardiopulmonary resuscitation (ECPR) programme in a moderately sized city. We described the 2014 OOHCA data and identified those who fulfilled hypothetical prehospital ECPR eligibility criteria. Methods: We identified patients aged 18–65 years in cardiac arrest, where CPR was commenced by paramedics on arrival. Traumatic cardiac arrest and end‐of‐life needs were patient exclusions. Patients were then included in one of three hypothetical 'ECPR eligible' groups. Patients were included in an 'ECPR eligible' group if they met author agreed criteria. Select patients in refractory VT/VF; pulseless electrical activity (PEA); and non‐refractory VT/VF, or asystole with subsequent VT/VF or transient return of spontaneous circulation (ROSC), were assigned to three separate groups. Descriptive statistics were applied to each group. Outcomes of ECPR eligible patients who developed sustained ROSC after 20 min of conventional CPR were characterised. Results: A total of 206 patients were included. A significant positive association between initial shockable rhythm (odds ratio [OR] 15.32, confidence interval [CI] 5.4–43.2) and sustained ROSC, and PEA (OR 6.93, CI 2.4–19.8) and sustained ROSC, versus asystole was identified ( P < 0.001). Sixty‐eight (33%) patients were eligible for one of the hypothetical ECPR groups. Twelve (17.6%) of the 68 ECPR eligible patients developed sustained ROSC after 20 min of conventional CPR, with only two surviving neurologically intact to hospital discharge. Conclusion: Sixty‐three (30.6%) patients could have derived benefit from a prehospital ECPR programme. Further analyses of prehospital ECPR logistics and economics are necessary to ensure that any future prehospital ECPR programme is effective and efficient.